Correlation of Carotid Artery Intima-Media Thickness with Calcium and Phosphorus Metabolism, Parathyroid Hormone, Microinflammatory State, and Cardiovascular Disease. (12th March 2022) - Huang, Peng; Tan, Junhua; Gu, Xianjun; Huang, Meiying; Huang, Feifan; Ma, Ruiying; Wang, Jie
Abstract : The internal thickness of the carotid artery is the vertical distance between the intima of the carotid artery and the middle mold. Its normal thickness is less than 1 mm. It can be used to judge the degree of arteriosclerosis. Under normal circumstances, the change of the internal thickness of the carotid artery is caused by cardiovascular disease. The purpose of this article is to study the relationship between the thickness of the carotid artery and the metabolism of calcium and phosphorus, parathyroid hormone, microinflammatory state, and cardiovascular disease. This article uses ultrasound measurement to measure the IMT of ESRD patients and carotid arteries with normal renal function. The analysis includes blood pressure, blood phosphorus, blood calcium, blood creatinine, blood urea nitrogen, blood sugar, glycosylated hemoglobin, blood lipids, parathyroid hormone, and C reaction. The correlation between clinical indicators includes protein and carotid IMT in ESRD patients which can be used in designing a diagnostic plan for patients through correlation research. The results showed that the carotid artery IMT of ESRD nondialysis patients was 13% thicker than that of those with normal renal function, and it was significantly positively correlated with age, blood pressure, blood phosphorus, glycosylated hemoglobin, and C-reactive protein. The correlation ratio with calcium and phosphorus was about 0.1.